Deepening visitor engagement with museum exhibits through hand-crafted visual markers - Ali, Susan; Koleva, Boriana; Bedwell, Ben; Benford, Steve (2018)
Visual markers, in particular QR codes, have become widely adopted in museums to enable low cost interactive applications. However, visitors often do not engage with them. In this paper we explore the application of visual makers that can be designed to be meaningful and that can be created by visitors themselves. We study both the use of these markers as labels for portraits that link to audio recordings and as a mechanism for visitors to contribute their own reflections to the exhibition by drawing a marker and linking an audio comment. Our findings show visitors appreciated the use of the aesthetic markers and engaged with them at three levels – physical placement, aesthetic content and digital content. We suggest that these different levels need to be considered in the design of future visiting systems, which make use of such markers, to ensure they are mutually supporting in shaping the experience.